اثر ألفية ابن مالك في تيسير تعلم وتعليم النحو: جامعة حمة الأخضر الوادي عينة - بداده، شيماء (جامعة حسيبة بن بوعلي بالشلف - كلية الآداب والفنون, 2018)
لظهور النحو أسباب عدة منها: انحراف لسان العرب في نطق الكلمات العربية، والمحافظة على سلامة نطق وقراءة القرآن الكريم، وحاجة الأعاجم إلى تعلم اللغة العربية لغة القرآن والدفاع عن اللغة العربية عندما دخل الأعاجم عن العرب بلغتهم؛ لذلك ظهرت حركة تدوين المتون النحوية في البيئة العربية دفاعا عن قواعد هذه اللغة، فاختارنا من هذه المتون ألفية ابن مالك ، وأردنا توضيح دور هذا المتن في عملية تعلم وتعليم النحو في المدارس الجزائرية، فتناولنا في هذا المقال: تعريفا لصاحب المتن، ووصفا لكتابه، وسلطنا الضوء على أهم الشروح لهذا المتن المهم، ووضحنا دور الألفية في عملية تبسيط وتيسير عملية تعلم وتعليم النحو.
The grammar has appcared because of mary reasons incloding : the arads tongvés wars in Arabic worads pronunciation .and preserving the safty of the pronvnciation and readingquran. And the need of learning Arabic by foreigners the language of quran. And defending the Arabic language when the foreigners entered on Arabs whith their own language. For that the movement of grammatical texts notation appeared at the Arabic environment as defend on this language. Roles. So we chose from among these texts, sonofmalik alphabet, and we warted to clarify the role of this text in Algerian schools, sowe addresses al this artille: adefinition of the text owner, and description to his write, and we have highlighted the most important explanations of this important text, and we clarify the role of the alphabet in the process of simplifying the process of learning and teaching the grammar.
Keywords: اللغة العربية -- النحو العربي -- ألفية ابن مالك -- ابن مالك، محمد بن عبدالله بن مالك، ت. 672 هـ -- تيسير النحو -- تعليم النحو